2022
DOI: 10.1186/s12943-022-01542-8
|View full text |Cite
|
Sign up to set email alerts
|

KMT2C methyltransferase domain regulated INK4A expression suppresses prostate cancer metastasis

Abstract: Background Frequent truncation mutations of the histone lysine N-methyltransferase KMT2C have been detected by whole exome sequencing studies in various cancers, including malignancies of the prostate. However, the biological consequences of these alterations in prostate cancer have not yet been elucidated. Methods To investigate the functional effects of these mutations, we deleted the C-terminal catalytic core motif of Kmt2c specifically in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 80 publications
0
31
0
Order By: Relevance
“…Although NCOR1 and KMT2C/D alterations were relatively common in this study ( Supplementary Figure 1 ), there were few studies investigating on their oncogenic role in BTC. Previous studies have found that NCOR1 and KMT2C/D play oncogenic roles in bladder cancer ( 24 ), colorectal cancer ( 25 ), prostate cancer ( 26 , 27 ), and lymphomagenesis ( 28 ). In addition, other important BTC genes, including PBRM1 (10%), BRAF (8%), BAP1 (6%), PTEN (5%), IDH1 (5%), IDH2 (5%), and NRAS (2%), were also identified with a relatively low prevalence in our cohort ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Although NCOR1 and KMT2C/D alterations were relatively common in this study ( Supplementary Figure 1 ), there were few studies investigating on their oncogenic role in BTC. Previous studies have found that NCOR1 and KMT2C/D play oncogenic roles in bladder cancer ( 24 ), colorectal cancer ( 25 ), prostate cancer ( 26 , 27 ), and lymphomagenesis ( 28 ). In addition, other important BTC genes, including PBRM1 (10%), BRAF (8%), BAP1 (6%), PTEN (5%), IDH1 (5%), IDH2 (5%), and NRAS (2%), were also identified with a relatively low prevalence in our cohort ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…KMT2C mutations contribute to tumorigenesis and are associated with poor survival rates (61,62). In particular, the complete loss of KMT2C due to truncating mutations is correlated with significantly shorter progression-free survival in patients with breast cancer patients who undergo estrogen therapy (63) and in patients with metastatic prostate cancer (64). The IPA-associated loss of KMT2C may have the functions that need further validation.…”
Section: Resultsmentioning
confidence: 99%
“…KMT2C mutations contribute to tumorigenesis and are associated with poor survival rates 55,56 . In particular, the complete loss of KMT2C due to truncating mutations is correlated with significantly shorter progression-free survival in patients with breast cancer patients who undergo estrogen therapy 57 and in patients with metastatic prostate cancer 58 . The IPAassociated loss of KMT2C may have the functions that need further validation.…”
Section: Correlations Between Truncating Mutations Ipa and Tumor Muta...mentioning
confidence: 99%